UPAYA GURU PEMBIMBING DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK TINGGAL KELAS DI SMP NEGERI KECAMATAN RANAH PESISIR - Asmaneli, Asmaneli; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
The research looked at the phenomenon of persistence of students who fail to learn even live classes due to lack of student interest in learning, lack of interest in following the lesson, do not the work assigned by the teacher. The problem in this student is how the tutor efforts in increasing the motivation of learners staying in SMP Negeri Kecamatan Ranah Pesisir. This students aims to describe the efforts tutor in improving learners intrinsic motivation and extrinsic motivation to learn and stay in the classroom. This research is a descriptive studentsâ that tried to describe a situation for what it is. The population in this studentsâ was the stayed in SMP Negeri Kecamatan Ranah Pesisir totaling 20 peoples. Samples were from the number of population. Sampling techniques, namely: total samplings are all populations. Sources of data in this research is primary data and secondary data. Association engineering data in this study using a questionnaire. The results of the data in this study were processed using techniques percentage. The findings of research that attempts tutor in improving learners intrinsic motivation to stay in the classroom learning with unfavorable criteria and guidance counselor efforts in improving the extrinsic motivation of learners in the classroom learning live on fewer criterions. The author suggests the guidance counselor for more openly and thoroughly to improve intrinsic and extrinsic motivation in SMP Negeri Kecamatan Ranah Pesisir achieve a good motivation to learn to get a good learning outcomes.